Can we predict postoperative complications in elderly Chinese patients with hip fractures using the surgical risk calculator? - Wang X (Dove Medical Press, 2017)
Xiao Wang, Bin Jiang Zhao, Yue Su Department of Anesthesiology, Beijing Shijitan Hospital, Capital Medical University, Beijing, China Purpose: Hip fractures are associated with poor prognosis in elderly patients partly due to the high rate of postoperative complications. This study was aimed to investigate whether the surgical risk calculator is suitable for predicting postoperative complications in elderly Chinese patients with hip fractures.Methods: The incidence of postoperative complications among 410 elderly patients with hip fractures was predicted by the surgical risk calculator and then compared with the actual value. The risk calculator model was evaluated using the following three metrics: Hosmer–Lemeshow test for the goodness-of-fit of the model, receiver operating characteristic curve (ROC) (also referred as C-statistic) for the predictive specificity and sensitivity, and the Brier’s score test for predictive accuracy.Results: Preoperative risk factors including gender, age, preoperative functional status, American Society of Anesthesiologists grade, hypertension, dyspnea, dialysis, previous cardiovascular history, and cerebrovascular disease were positively correlated with the incidence of postoperative complications in elderly patients with hip fractures. The predicted complication incidence rate was well matched with the actual complication rate by Hosmer–Lemeshow test. The model had high sensitivity and specificity for predicting the mortality rate of these patients with a C-statistic index of 0.931 (95% CI [0.883, 0.980]). The surgical calculator model had an accuracy of 90% for predicting the reoperation rate (Brier’s score <0.01).Conclusions: The surgical risk calculator could be useful for predicting mortality and reoperation in elderly patients with hip fracture. Patients and surgeons may use this simple calculator to better manage the preoperative risks. Keywords: hip fracture, femoral head fracture, elder age, surgical risk calculator, ACS-NSQIP